Aerosol Induced Changes in Sea Surface Temperature Over the Bay of Bengal Due to COVID-19 Lockdown - Sarin, T. S.; Vinoj, V.; Swain, D.; Landu, K.; Suhas, E. (Frontiers in Marine Science, 2021)
The role of COVID-19 pandemic lockdown in improving air quality was reported extensively for land regions globally. However, limited studies have explored these over oceanic areas close to high anthropogenic activities and emissions. The Bay of Bengal (BoB) basin is one such region adjacent to the highly populated South Asian region. We find that Aerosol Optical Depth (AOD) over the BoB declined by as much as 0.1 or 30% during the peak lockdown of April 2020 compared to long-term climatology during 2003–2019. Simultaneously, the sea surface temperature (SST) rose by 0.5–1.5°C over the central and north-western parts of the BoB with an average increase of 0.83°C. We show that up to 30% of this observed warming is attributable to reduced atmospheric aerosols. The study highlights the importance of anthropogenic emissions reduction due to COVID lockdown on short-term changes to SST over ocean basins with implications to regional weather.